Accelerated orthodontic treatment using photobiomodulation: A randomized clinical trial - Mohammad K Alam; Balqees Alahmari (Wolters Kluwer Medknow Publications, 2024)
Background: Orthodontic treatment (OT) aims to align and correct teeth positions. However, conventional treatment methods often require a considerable amount of time. Photobiomodulation (PBM) has emerged as a potential solution to OT. Materials and Methods: The study included 60 patients, divided equally into two groups: the PBM group and the control group. Patients in the PBM group received light therapy sessions applied directly to the OT area during each visit. Both groups underwent regular orthodontic adjustments. Treatment duration, changes in tooth alignment, and patient discomfort were evaluated. Statistical analysis was performed to compare the outcomes between the groups. Results: The results of the study indicated that the PBM group experienced a statistically significant reduction in treatment duration compared to the control group. Moreover, there were noticeable improvements in tooth alignment in both groups. Patients in the PBM group reported minimal discomfort during the treatment process. These findings suggest that PBM has the potential to expedite OT without compromising its effectiveness. Conclusion: In conclusion, this randomized clinical trial demonstrates that PBM can be an effective approach to accelerate OT. The technique led to a significant reduction in treatment duration and was well-tolerated by patients.